2016
DOI: 10.1016/j.stem.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Instability in Human Pluripotent Stem Cells Arises from Replicative Stress and Chromosome Condensation Defects

Abstract: Human pluripotent stem cells (hPSCs) frequently acquire chromosomal aberrations such as aneuploidy in culture. These aberrations progressively increase over time and may compromise the properties and clinical utility of the cells. The underlying mechanisms that drive initial genomic instability and its continued progression are largely unknown. Here, we show that aneuploid hPSCs undergo DNA replication stress, resulting in defective chromosome condensation and segregation. Aneuploid hPSCs show altered levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
85
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 26 publications
6
85
0
Order By: Relevance
“…That study specified that Smc5/6 is required to resolve recombination structures formed from endogenous replication stress and late replication pausing sites. Human PSCs are prone to genomic instability due to replicative stress and impaired chromosome condensation (Lamm et al, 2015). It is likely that Smc5/6 plays a crucial role in avoiding these sources of genomic instability in PSCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That study specified that Smc5/6 is required to resolve recombination structures formed from endogenous replication stress and late replication pausing sites. Human PSCs are prone to genomic instability due to replicative stress and impaired chromosome condensation (Lamm et al, 2015). It is likely that Smc5/6 plays a crucial role in avoiding these sources of genomic instability in PSCs.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study employing human somatic RPE-1 cells has demonstrated the requirement of Smc5/6 complex for timely progression of DNA synthesis (Gallego-Paez et al, 2014). Given that DNA replication stress can further cause defects in stem cell chromosome condensation and abnormal segregation (Lamm et al, 2015), we synchronized mESCs in the G1 phase of cell cycle and observed the progression through the S phase (Fig. 4E).…”
Section: Smc5-deficient Mescs Undergo Mitotic Catastrophementioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, we set out to study replication dynamics in aneuploid hPSCs by taking advantage on the DNA combing method. We found that aneuploid hPSCs (either harboring trisomy 12, 17 or both) exhibit inherent perturbed DNA replication characterized by a slow replication rate and activation of dormant origins (6). Interestingly, a recent work showed that aneuploidy induces replication stress also in somatic cells (8).…”
mentioning
confidence: 84%
“…Indeed, hPSCs harboring these recurrent aneuploidies show higher tumorigenic potential and on-going chromosomal instability similar to chromosome instability (CIN + ) cancer cells. Therefore, we were intrigued to investigate the cellular mechanisms underlying the on-going instability and tumorigenicity induced by these aneuploidies (6).…”
mentioning
confidence: 99%